Elbow Joint Radiography with Suspection of Olecranon Process Fracture in the Hospital Columbia Asia Medan - Tarigan, Liberti; Pasaribu, Parsaoran (PT Inovasi Pratama Internasional, 2023)
Elbow Joint Radiography with a suspected Olecranon Process Fracture , in order to get an optimal image requires the right equipment to support the smooth running of health services such as using a General X-ray Unit X-ray. The aim of elbow joint radiography research is to show the anatomy and obtain a radiographic picture of the elbow joint with abnormalities that occur in the elbow joint. The type of research used is descriptive qualitative research. Qualitative research techniques are research that is descriptive in nature and tends to use analysis and the subject's perspective is emphasized more. The results obtained from a radiographic examination of the elbow joint with suspected olecranon process fracture using a machine with a capacity of 500mA. In radiographs of elbow joints with suspected olecranon process fractures, it is necessary to adjust the size of the radiation field as needed so that the radiation dose received by the patient is smaller.